Legal Reconstruction of the Oversight of Government Officials’ Discretion in the Context of Preventing Abuse of Authority and Safeguarding the Public Interest - I Made Juni Artawan; Zainal Arifin Hoesein (SULTAN ADAM: Jurnal Hukum dan Sosial, 2026)
This study aims to analyze the regulation and implementation of discretionary supervision of government officials in the Indonesian state administrative law system, identify problems that hinder the effectiveness of preventing the abuse of authority, and formulate a legal reconstruction model for discretionary supervision to provide optimal protection of the public interest. The study uses a normative juridical method, employing a statutory and conceptual approach through analysis of laws and regulations, doctrines, and theories of state administrative law. The results of the study indicate that discretionary supervision still faces various problems in the form of unclear parameters for abuse of authority, overlapping authority between the Government Internal Supervisory Apparatus (APIP), the Ombudsman of the Republic of Indonesia, the State Administrative Court, and law enforcement officials, and a lack of integration of the supervisory system that causes legal uncertainty. These conditions have the potential to lead to maladministration, state losses, and violations of public rights. The proposed legal reconstruction is carried out through strengthening preventive supervision, harmonizing the authority of supervisory institutions, establishing clear indicators regarding abuse of authority, providing legal protection for officials who act in good faith, and developing an information technology-based supervisory system. This model is expected to be able to realize legal certainty, justice, benefit, and protection of public interests in the administration of government.